2006
DOI: 10.1038/sj.bjc.6603327
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in metastatic renal cell carcinoma: metastasectomy as independent prognostic variable

Abstract: Prognostic and predictive factors in patients with metastatic renal cell carcinoma (MRCC) have been evaluated from untreated patients or patients on several different treatment approaches. The aim of this analysis was to define prognostic and predictive factors in patients treated uniformly with a low-dose outpatient cytokine combination. The relationship between patient-, tumour-, and treatment-related factors was analysed in 99 patients with MRCC. These features were first examined in univariate analyses, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 25 publications
3
52
0
2
Order By: Relevance
“…39,42 Given this longer survival, some authors have advocated en bloc resection, arguing that eradication of the single active site of disease may play a role in improving quality of life and even survival. 2,20,27,29,44 We offer what we believe is the first report providing information about the natural history of surgical patients presenting with a solitary metastasis of RCC to the spine. We found that 75% of these cases will develop an additional disease site (spinal or extraspinal) within a median interval of 12.2 months after the initial spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…39,42 Given this longer survival, some authors have advocated en bloc resection, arguing that eradication of the single active site of disease may play a role in improving quality of life and even survival. 2,20,27,29,44 We offer what we believe is the first report providing information about the natural history of surgical patients presenting with a solitary metastasis of RCC to the spine. We found that 75% of these cases will develop an additional disease site (spinal or extraspinal) within a median interval of 12.2 months after the initial spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…60 Although the response rate itself is not considered a good surrogate for OS in metastatic RCC, 61 CRP is not only a predictive marker for response, but also a significant prognostic indicator for survival in patients with metastatic RCC. [51][52][53]55,62 In a large Japanese multicenter cohort of 1463 metastatic RCC patients, 62 CRP had significant prognostic impact on OS, as well as time from initial visit to metastasis, Eastern Cooperative Oncology Group Performance Status, serum lactate dehydrogenase and Ca level, all of which were included in the MSKCC criteria. 63 The 1-year OS rate of 598 patients with elevated CRP levels (>3 mg/L) was 55%, compared with 84.7% of 266 patients without those.…”
Section: Prognostic Value Of Crp In Renal Cell Carcinomamentioning
confidence: 99%
“…25 Additionally, metastasectomy should be considered for patients with solitary lung, bone or brain metastases and a potentially resectable primary tumor as well as for patients with a solitary recurrence after a long diseasefree interval. 26,27 Radiotherapy and chemotherapy is barely effective and should be mainly considered as palliative treatment in RCC patients. Unspecific immunotherapy, mostly consisting of interleukin (IL)-2 and/or interferon (IFN)-a with or without 5-fluorouracil (5-FU) has been the only systemic treatment option for many years leading to clinical improvements in a small proportion of patients, however at the cost of substantial toxicities.…”
Section: Introductionmentioning
confidence: 99%